2016
DOI: 10.1002/etc.3629
|View full text |Cite
|
Sign up to set email alerts
|

Responses of juvenile southern flounder exposed to Deepwater Horizon oil‐contaminated sediments

Abstract: The Deepwater Horizon oil spill released millions of barrels of crude oil into the northern Gulf of Mexico, much of which remains associated with sediments and can have continuing impacts on biota. Juvenile southern flounder (Paralichthys lethostigma) were exposed for 28 d in the laboratory under controlled conditions to reference and Deepwater Horizon oil-contaminated sediments collected from coastal Louisiana to assess the impacts on an ecologically and commercially important benthic fish. The measured polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Although the southern flounder in the present study had relatively high biotransformation rates for phenanthrene, they hypothetically suffered from metabolic fatigue and consequently, mortality. Moreover, southern flounder have been shown to have severe adverse effects across multiple endpoints when exposed to environmentally relevant concentrations of Deepwater Horizon –contaminated sediment .…”
Section: Discussionmentioning
confidence: 99%
“…Although the southern flounder in the present study had relatively high biotransformation rates for phenanthrene, they hypothetically suffered from metabolic fatigue and consequently, mortality. Moreover, southern flounder have been shown to have severe adverse effects across multiple endpoints when exposed to environmentally relevant concentrations of Deepwater Horizon –contaminated sediment .…”
Section: Discussionmentioning
confidence: 99%
“…Composite sediment and water samples were analyzed for PAH composition following the procedure discussed in Brown-Peterson et al (2015) ( S2 Table ). This concentration was selected as it is environmentally relevant to the Gulf Coast following the oil spill [ 43 ] and is a concentration we have previously demonstrated to have adverse effects in flounder [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effects of some environmental chemical contaminants on the microbiome of aquatic organisms have been investigated on a limited basis (Table ). Examples include triclosan, the heavy metal cadmium, PAHs, nanomaterials, and the fungicide imazalil (Gaulke et al ; Brown‐Peterson et al ; Jin C et al ; Zhai et al ), to name a few. Studies have identified a number of operational taxonomic units from phyla to genera that can change in abundance in the gut following contaminant exposures (Table ).…”
Section: Case Studies Investigating the Microbiome In Aquatic Toxicologymentioning
confidence: 99%
“…In the aftermath of the 2010 Deepwater Horizon oil spill, there were many reports demonstrating that the incursion of oil altered the microbial population spectrum of water and sediment significantly as a function of both time and distance from the oil release (Hazen et al ; Kostka et al ; Dubinsky et al ; Gutierrez et al ; Looper et al ; Mason et al ). However, there was relatively little research aimed at understanding the effects of oil contamination on the microbiomes of fish species in the affected area (Barron ; Whitehead et al ; Barron et al ; Brewton et al ; Brown‐Peterson et al ). This was somewhat surprising, given that there is increasing evidence that exogenous factors can have significant effects on the microbiome of organisms (Carlson et al ; Gaulke et al ).…”
Section: Case Studies Investigating the Microbiome In Aquatic Toxicologymentioning
confidence: 99%